Dihydronicotinamide Riboside Is a Potent NAD+ Precursor Promoting a Pro-Inflammatory Phenotype in Macrophages - Chini, Claudia C. S.; Peclat, Thais R.; Gomez, Lilian S.; Zeidler, Julianna D.; Warner, Gina M.; Kashyap, Sonu; Mazdeh, Delaram Z.; Hayat, Faisal; Migaud, Marie E.; Paulus, Aneel; Chanan-Khan, Asher A.; Chini, Eduardo N. (Frontiers in Immunology, 2022)
Nicotinamide adenine dinucleotide (NAD) metabolism plays an important role in the regulation of immune function. However, a complete picture of how NAD, its metabolites, precursors, and metabolizing enzymes work together in regulating immune function and inflammatory diseases is still not fully understood. Surprisingly, few studies have compared the effect of different forms of vitamin B3 on cellular functions. Therefore, we investigated the role of NAD boosting in the regulation of macrophage activation and function using different NAD precursors supplementation. We compared nicotinamide mononucleotide (NMN), nicotinamide riboside (NR), and nicotinamide (NAM) supplementation, with the recently described potent NAD precursor NRH. Our results show that only NRH supplementation strongly increased NAD+ levels in both bone marrow-derived and THP-1 macrophages. Importantly, NRH supplementation activated a pro-inflammatory phenotype in resting macrophages, inducing gene expression of several cytokines, chemokines, and enzymes. NRH also potentiated the effect of lipopolysaccharide (LPS) on macrophage activation and cytokine gene expression, suggesting that potent NAD+ precursors can promote inflammation in macrophages. The effect of NRH in NAD+ boosting and gene expression was blocked by inhibitors of adenosine kinase, equilibrative nucleoside transporters (ENT), and IκB kinase (IKK). Interestingly, the IKK inhibitor, BMS-345541, blocked the mRNA expression of several enzymes and transporters involved in the NAD boosting effect of NRH, indicating that IKK is also a regulator of NAD metabolism. In conclusion, NAD precursors such as NRH may be important tools to understand the role of NAD and NADH metabolism in the inflammatory process of other immune cells, and to reprogram immune cells to a pro-inflammatory phenotype, such as the M2 to M1 switch in macrophage reprogramming, in the cancer microenvironment.